2022
DOI: 10.3390/ijerph20010706
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis in COVID-19-Positive Children: Report of 4 Cases from an Endemic Area in Northeastern Romania

Abstract: Acute appendicitis (AA) is one of the most common surgical emergencies in children. Some reports have suggested that the COVID-19 pandemic was responsible for delays in the diagnostic and proper treatment of AA in pediatric patients. The aim of our study was to perform a retrospective study of cases of AA in children with SARS-CoV-2 infection treated in a highly endemic area for COVID-19 in Romania during a 2-year time interval. The SARS-CoV-2 infection had no unfavorable impact on children who presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Four (4) patients from this group were diagnosed with acute appendicitis and they were included in a previous article. [ 30 ] The main data related to the remaining 14 patients are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four (4) patients from this group were diagnosed with acute appendicitis and they were included in a previous article. [ 30 ] The main data related to the remaining 14 patients are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The methodology of the study was similar to the one reported in previous studies. [29][30][31] Informed consent for treatment and data sharing/ publication had been obtained in all cases from the legal guardians at admission, in order to make use of these data for research purposes. Consent from the Ethical Committee of the hospital was obtained and the patients were deidentified.…”
Section: Methodsmentioning
confidence: 99%
“…In Romania, one of the first authors to observe that the differences between patients with severe and non-severe cases were not statistically significant was Totan et al [56]. Other studies had similar findings [28,32,60].…”
Section: Transaminase Levels and Other Hepatic Markersmentioning
confidence: 94%
“…A recently observed new variant, mimicking AA, 11 13 prompts abdominal imaging and surgical evaluation. Pediatric surgeons must first be aware of the GI symptoms of MIS-C to diagnose it correctly.…”
Section: Introductionmentioning
confidence: 99%
“…8 Children with COVID-19 have reported receiving non-operative therapy for simple AA with antibiotics. 9,10 A recently observed new variant, mimicking AA, [11][12][13] prompts abdominal imaging and surgical evaluation. Pediatric surgeons must first be aware of the GI symptoms of MIS-C to diagnose it correctly.…”
Section: Introductionmentioning
confidence: 99%